Promising Therapeutic Strategies Targeting Mitochondria in Kidney Diseases: From Small Molecules to Whole Mitochondria - Alexis Paulina Jiménez-Uribe; José Pedraza-Chaverri (MDPI AG, 2022)
Kidney function highly depends on mitochondria, organelles that regulate different metabolic pathways. Mitochondria-altered function and structure are present during acute kidney injury (AKI) and chronic kidney disease (CKD). Targeting mitochondria using several strategies has been shown to improve kidney function. Here, we review some experimental mitochondria targeting strategies with clinical potential in kidney diseases encompassing cationic/lipophilic small molecules, peptides, nanocarriers, and even the entire organelle.